Risk of fatty liver after long-term use of tamoxifen in patients with breast cancer. - Jeong-Ju Yoo; Yong Seok Lim; Min Sung Kim; Bora Lee; Bo-Yeon Kim; Zisun Kim; Ji Eun Lee; Min Hee Lee; Sang Gyune Kim; Young Seok Kim (PLoS ONE, 2020)
Background Few studies report the effects of tamoxifen intake and the occurrence of de novo fatty liver and the deterioration of existing fatty liver. The aim of this study was to investigate the effects of tamoxifen on fatty change of liver over time and also the impact of fatty liver on the prognosis of patients with breast cancer. Methods This was a single-center, retrospective study of patients who were diagnosed with primary breast cancer from January 2007 to July 2017. 911 consecutive patients were classified into three groups according to treatment method: tamoxifen group, aromatase inhibitor (AI) group, and control group. Results Median treatment duration was 49 months (interquartile range, IQR; 32-58) and median observational period was 85 months (IQR; 50-118). Long-term use of tamoxifen significantly aggravated fatty liver status compared to AI or control groups [hazard ratio (HR): 1.598, 95% confidence interval (CI): 1.173-2.177, P = 0.003] after adjusting other factors. When analyzed separately depending on pre-existing fatty liver at baseline, tamoxifen was involved in the development of de novo fatty liver [HR: 1.519, 95% CI: 1.100-2.098, P = 0.011) and had greater effect on fatty liver worsening (HR: 2.103, 95% CI: 1.156-3.826, P = 0.015). However, the progression of fatty liver did not significantly affect the mortality of breast cancer patients. Conclusions Tamoxifen had a significant effect on the fatty liver status compared to other treatment modalities in breast cancer patients. Although fatty liver did not affect the prognosis of breast cancer, meticulous attention to cardiovascular disease or other metabolic disease should be paid when used for a long time.